Donald Duck is back, and he speaks spanish - Martí, Luisa (Proceedings of the Amsterdam Colloquium, 2005)
This paper argues that the solution to the “Donald Duck” problem put forth in Schwarzschild 2002 is, despite its simplicity and attractiveness, not viable. Schwarzschild’s solution to the problem involves the idea that the domain restriction of indefinites can be a singleton set. This assumption not only solves the “Donald Duck” problem, it also explains why indefinites can take scope outside of syntactic islands in many languages. I show with data from Spanish, however, that there are indefinites whose wide scope is sensitive to islands. If wide scope readings are analyzed using the singleton-set idea, however, their sensitivity to the syntactic environment in Spanish cannot be explained. This suggests that we should reject this assumption. But if so, we no longer have a general solution to the “Donald Duck” problem. I then suggest that solutions to the problem that exploit the semantics of conditionals are to be preferred.